2015
DOI: 10.2196/resprot.3996
|View full text |Cite
|
Sign up to set email alerts
|

Using Facebook to Recruit Young Adult Veterans: Online Mental Health Research

Abstract: BackgroundVeteran research has primarily been conducted with clinical samples and those already involved in health care systems, but much is to be learned about veterans in the community. Facebook is a novel yet largely unexplored avenue for recruiting veteran participants for epidemiological and clinical studies.ObjectiveIn this study, we utilized Facebook to recruit a sample of young adult veterans for the first phase of an online alcohol intervention study. We describe the successful Facebook recruitment pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 52 publications
5
101
0
Order By: Relevance
“…To be eligible, individuals needed to be age 18 or older, and on active duty in the U.S. Armed Forces after September 2001 but not presently. We excluded individuals who completed surveys in less than five minutes, had more than one survey response, or incorrectly answered a military-related 'insider knowledge' question (to reduce chance of online survey misrepresentation) [19,27]. Survey completion was defined as those respondents who reached the end of the online survey and were not excluded based on the above quality control measures.…”
Section: Methods Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…To be eligible, individuals needed to be age 18 or older, and on active duty in the U.S. Armed Forces after September 2001 but not presently. We excluded individuals who completed surveys in less than five minutes, had more than one survey response, or incorrectly answered a military-related 'insider knowledge' question (to reduce chance of online survey misrepresentation) [19,27]. Survey completion was defined as those respondents who reached the end of the online survey and were not excluded based on the above quality control measures.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Facebook ads have been used effectively in populations including college students and young adults [16,17] and military veterans (particularly those with risky drinking) [18][19][20][21]. Prior research has also suggested ad campaigns can achieve both "broad reach and targeted recruitment," and found ad costs to be manageable [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final sample included 812 veterans aged 19-34 who had previously served in the U.S. Air Force, Army, Marines or Navy (Pedersen et al, 2015). This sample excluded those who were still serving in the National Guard or Reserves.…”
Section: Samples and Participantsmentioning
confidence: 99%